NABIZ DALGA HIZININ FRAMİNGHAM RİSK SKORLAMASI, SCORE RİSK DEĞERLENDİRME SİSTEMİ VE VİSSERAL ADİPOZİTE İNDEKSİ İLE İLİŞKİSİNİN ARAŞTIRILMASI - ÇELENK, YUSUF BİLAL (Fırat Üniveristesi, 2023)
Kardiyovasküler hastalıklar, ülkemizde ve dünyada mortalite ve morbiditenin başta gelen sebeplerindendir. Kardiyovasküler risk skorlama yöntemleri sayesinde risk altındaki popülasyon erkenden tespit edilebilemekte ve risk faktörlerine zamanında müdahale edilebilmektedir. Arteriyel sertliğin ölçümü de kardiyovasküler hastalıkların tespitinde ve önlenmesinde giderek önem kazanmaktadır. Antropometrik ölçümlere ve klinik parametrelere dayanan visseral adipozite indeksi, kardiyovasküler hastalıklar ile yakından ilişkili olan visseral adipoz doku hakkında bilgi veren basit bir hesaplama metodudur. Çalışmamız arteriyel sertlik ile kardiyovasküler hastalık risk skorları ve visseral adipozite indeksi arasındaki ilişkiyi araştırmayı amaçlamaktadır. Çalışmamıza 40-69 yaş arasında, daha önce kardiyovasküler hastalık öyküsü olmayan 209 kişi dahil edilmiştir. Çalışmaya katılan kişilerin nabız dalga hızları ölçülmüş, Framingham ve SCORE2 risk skorları hesaplanmış, visseral adipozite indeksi değerleri belirlenmiştir. Çalışmamıza katılan kişilerin yaş ortalaması 52,9±8,1'di, %53,1'i kadın, %46,9'u erkekti. Katılımcıların nabız dalga hızı ortanca değeri 7,6 m/s, Framingham risk skoru ortanca değeri %9, SCORE2 risk skoru ortanca değeri %4,9, Visseral adipozite indeksi ortanca değeri ise 5,24'tü. Framingham Risk Skoru ve SCORE2 Risk Skoru ile nabız dalga hızı arasında anlamlı ilişki saptandı (p<0,001, p<0,001). Arteriyel sertlik ile visseral adipozite indeksi arasında anlamlı bir ilişki saptanmadı (p=0,184). Framingham Risk Skoru'na göre düşük,orta riskli grubu ayırt etmede 7,6 m/s, orta ve yüksek riskli grubu ayırt etmede 8,2 m/s kesme değerleri belirlendi. SCORE2 Risk Skoru için düşük-orta ile yüksek riskli grubu ayırt etmede 7,8 m/s, yüksek ile çok yüksek riskli grubu ayırt etmede 8,9 m/s kesme değerleri tespit edildi. Sonuç olarak çalışmamız arteriyel sertlik ölçümünün, kardiyovasküler riski belirlemede güçlü bir parametre olduğu göstermiş ve klinikte daha yaygın şekilde kullanılmasına fayda sağlayacak kesme değerleri belirlemiştir. Anahtar kelimeler: Arteriyel sertlik, nabız dalga hızı, Framingham Risk Skoru, SCORE2 Risk Skoru, visseral adipozite indeksi

Cardiovascular diseases are among the leading causes of mortality and morbidity in our country and in the world. With cardiovascular risk scoring methods, the population at risk can be detected early and risk factors can be intervened in a timely manner. Measurement of arterial stiffness is also gaining importance in the detection and prevention of cardiovascular diseases. Visceral adiposity index, based on anthropometric measurements and clinical parameters, is a simple calculation method that provides information about visceral adipose tissue, which is closely related to cardiovascular diseases. Our study aimed to investigate the relationship between arterial stiffness, cardiovascular disease risk scores and visceral adiposity index. Our study included 209 people aged 40-69 years without a history of cardiovascular disease. Pulse wave velocities of the participants were measured, Framingham and SCORE2 risk scores were calculated, and visceral adiposity index values were determined. The mean age of the participants in our study was 52.9±8.1 years, 53.1% were female and 46.9% were male. The median value of the pulse wave velocity of the participants was 7.6 m/s, the median value of the Framingham risk score was 9%, the median value of the SCORE2 risk score was 4.9%, and the median value of the visceral adiposity index was 5.24. A significant correlation was found between pulse wave velocity and cardiovascular disease risk scores (p<0,001, p<0,001). No significant correlation was found between arterial stiffness and visceral adiposity index (p=0,184). According to the Framingham Risk Score, cut-off values of 7.6 m/s were determined to distinguish the low- and medium-risk groups, and 8.2 m/s to distinguish between the medium and high-risk groups. According to the Framingham Risk Score, the cut-off value was determined as 7.6 m/s for distinguishing the low and medium risk group, and 8.2 m/s for distinguishing the medium and high risk group. The cut-off value for the SCORE2 Risk Score was 7.8 m/s for distinguishing between low-intermediate and high-risk groups, and 8.9 m/s for distinguishing between high and very high-risk groups. In conclusion, our study showed that arterial stiffness measurement is a powerful parameter in determining cardiovascular risk and determined cut-off values that would benefit its more widespread use in the clinic. Key words: Arterial stiffness, pulse wave velocity, Framingham Risk Score, SCORE2 Risk Score, visceral adiposity index
Investigation of the relationship between pulse wave velocity, framingham risk scorings, score risk scorings and visceral adiposity index
Keywords: Aile Hekimliği